Research on Even Flow of High-power IGBT Module in Parallel - QI Shanjun; WENG Xingfang; SONG Wenjuan; HUANG Nan (Kongzhi Yu Xinxi Jishu)
The higher load current can be withstood when the high-power IGBT running in parallel. But the even flow problems of static and dynamic state require consideration when designing high-power IGBT in parallel. By PSpice simulation, the main factors affecting the static even flow are found, which include saturation voltage drop, collector and emitter’s lead equivalent resistance of IGBT module. The main factors affecting the dynamic even flow involve drive circuit, IGBT device parameters and main circuit layout. The solution of IGBT even flow in parallel is proposed. The key points of IGBT parallel circuit design are analyzed. By simulation, the feasibility of the proposed method is verified.